High Temporal Summation of Pain Predicts Immediate Analgesic Effect of Acupuncture in Chronic Pain Patients—A Prospective Cohort Study - Baeumler, Petra Iris; Conzen, Peter; Irnich, Dominik (Frontiers in Neuroscience, 2019)
Objectives This prospective cohort study explored whether two distinguished sensory parameters predicted acupuncture effects in chronic pain patients; namely high temporal summation of pain (TS) indicating spinal synaptic facilitation as well as a low vibration detection threshold (VDT) indicating a loss of Aβ-fiber function. Methods Pinprick induced TS and VDT were assessed by standardized, validated methods at the most painful body site and a pain free control site in 100 chronic pain patients receiving six acupuncture sessions as part of an interdisciplinary multimodal pain treatment (IMPT). Immediate change in pain intensity after the first acupuncture session (first treatment on the first day of IMPT) was assessed by the verbal rating scale (VRS, 0-100). After four weeks of treatment, patients indicated in a questionnaire whether acupuncture had relieved pain immediately and whether it had contributed to overall pain reduction and wellbeing after IMPT. Results Logistic regression analysis revealed an association between high TS at the control site and a reduction in pain intensity of at least 30% (VRS) after the first acupuncture (OR [95%-CI] 4.3 [1.6-11.8]). Questionnaire ratings of immediate pain relief after acupuncture were associated with high TS at the control site (OR [95%-CI] 3.8 [1.4-10.2] any pain relief, OR [95%-CI] 5.5 [1.7-17.1] over 50% pain reduction) and at the pain site (OR [95%-CI] 3.2 [1.2-8.9] any pain relief). Appraisals of the contribution of acupuncture to overall pain reduction and wellbeing after IMPT were not associated with TS. The VDT was not associated with any outcome. DiscussionConclusion This explorative study provides first-time evidence that high TS, especially at a pain free control site, but not VDT, might predict immediate analgesic response to acupuncture in chronic pain patients. Thus, highly centrally sensitized chronic pain patients might respond particularly well to acupuncture.